Filsafat Peran Filsafat Pendidikan dalam Pembelajaran Ilmu Kompter: Tinjauan Sistematis Literatur - Ully, Rona (Peneliti.net, 2025)
The philosophy of education has a very important role in shaping the learning paradigm in various disciplines, including computer science, which is currently one of the most relevant fields of study in the ever-evolving digital era. With society's increasing reliance on information technology, education in the field of computer science must be able to prepare individuals who not only have technical skills, but also a deep understanding of the basic concepts and ethics that come with them. This study aims to explore the integration of educational philosophy in the context of computer science learning through a systematic review of existing literature. This study uses the literature review method with descriptive analysis techniques. The results of the study show that the philosophy of education serves as a guide in designing the curriculum as well as the basis for developing effective learning strategies. The constructivist approach, which emphasizes the active role of students in the learning process, becomes one of the main focuses, where students are invited to be directly involved in building their own knowledge. Through this philosophical approach, educators can formulate strategies that focus not only on knowledge transfer, but also on the development of students' character and critical thinking. Thus, the application of the principles of educational philosophy can create a holistic and dynamic learning environment, better preparing students to face the challenges of future technology.